2010
DOI: 10.1007/s13277-010-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tumor marker HE4 is differently expressed during the phases of the menstrual cycle in healthy young women

Abstract: The objective of the present study was to investigate in healthy young women the fluctuations in serum concentration of human epididymal secretory protein human epididymis-specific protein 4 (HE4) and CA125 during the phases of the menstrual cycle and the correlation between HE4 and CA125 values and age. Forty women with regular menstrual cycles were included in the study. Pelvic and transvaginal ultrasound were performed in order to exclude ovarian pathologies. Blood samples were collected at follicular (FP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 25 publications
0
48
0
Order By: Relevance
“…This statistically significant difference was not observed in patients > 35 years. Serum CA125 level was not significantly different considering different phases of the menstrual cycle in both age groups [20].…”
Section: Discussionmentioning
confidence: 76%
“…This statistically significant difference was not observed in patients > 35 years. Serum CA125 level was not significantly different considering different phases of the menstrual cycle in both age groups [20].…”
Section: Discussionmentioning
confidence: 76%
“…Anastasi et al enrolled 50 women with regular menstrual cycles, aged 20-49 years, and measured their serum HE4 levels at postmenstrual days 7, 14, and 21 [44]. They found that serum HE4 levels fluctuated during the phase of menstrual cycle, and the highest levels were detected in the ovulatory phase (45.3 ± 1.19 pM) in comparison to the follicular (39.1 ± 1.1 pM) and luteal phases (42.0 ± 1.3 pM) in women younger than 35 years.…”
Section: He4 Levels In Female Reproductive Cyclesmentioning
confidence: 99%
“…The diagnostic sensitivity of CA 125 in ovarian cancer is related to tumor stage, with abnormal CA 125 serum concentrations seen in approximately 50% of patients with stage I disease and 80%-90% of patients with stages III-IV disease (3)(4)(5)(6)(7)(8)(9). However, the most important problem with CA 125 is its low diagnostic specificity, with abnormally high concentrations found in malignancies of different origin, including nonovarian gynecologic cancers (endometrium, endocervix), other epithelial tumors (lung cancer), and nonepithelial malignancies such as lymphomas (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). High serum CA 125 concentrations may be also found in several benign diseases, including effusions, liver or renal failure, and several benign gynecologic conditions such as ovarian cysts, myomas, and, primarily in premenopausal women, endometriosis (3,4,(7)(8)(9)16 ).…”
mentioning
confidence: 99%
“…However, the most important problem with CA 125 is its low diagnostic specificity, with abnormally high concentrations found in malignancies of different origin, including nonovarian gynecologic cancers (endometrium, endocervix), other epithelial tumors (lung cancer), and nonepithelial malignancies such as lymphomas (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). High serum CA 125 concentrations may be also found in several benign diseases, including effusions, liver or renal failure, and several benign gynecologic conditions such as ovarian cysts, myomas, and, primarily in premenopausal women, endometriosis (3,4,(7)(8)(9)16 ). Likewise, CA 125 concentrations may fluctuate throughout the menstrual cycle and pregnancy (16 -18 ).…”
mentioning
confidence: 99%